Time to address the shortcomings of the banking union - Ignazio Angeloni (Leibniz Institute for Financial Research SAFE, 2020)
Discussions about the banking union have restarted. Its success so far is limited: national banking sectors are still overwhelmingly exposed to their own countries' economies, cross border banking has not increased and capital and liquidity remain locked within national boundaries. The policy letter highlights that the current debate, centered on sovereign exposures and deposit insurance, misses critical underlying problems in the supervision and resolution frameworks. The ECB supervisors' efforts to facilitate cross-border banking have been hampered by national ringfencing. The resolution framework is not up to its task: limited powers of the SRB, prohibitive access conditions and limited size of the Single Resolution Fund limit its effectiveness. A lack of a coherent European framework for insolvency unlevels the regulatory field and creates incentives to bypass European rules. The new Commission and European Parliament, with the new ECB leadership, provide a unique opportunity to address these shortcomings and make the banking union work.
Keywords: 330; ECB; Banking Union; Cross-border Banking; Banking Supervision; Banking Resolution